JURIDICAL REVIEW OF LAW ENFORCEMENT OF ONLINE GAMBLING CRIMES AS CYBERCRIMES BASED ON LAW NUMBER 1 OF 2024 CONCERNING INFORMATION AND ELECTRONIC TRANSACTIONS - Jafri Aziz (Proceeding International Conference on Social Sciences, 2026)
The development of information technology in the digital era has given rise to various new forms of crime known as cyber crime, one of which is the practice of online gambling. These crimes not only violate legal and moral norms, but also cause serious social, economic, and psychological repercussions for society. These crimes involve perpetrators and victims from different countries and do not only occur domestically. This phenomenon shows that there is an increase every year in online gambling enthusiasts both among all ages regardless of the limits. For the eradication of online gambling, a strong criminal law policy is needed to handle and prevent cybercrime because the impact is real on losses in terms of finance and time. Based on Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE), this study investigates law enforcement against cyber crime perpetrators. In this study, a normative juridical approach is used, which evaluates the provisions of relevant laws and regulations and legal doctrines. The results of the study show that although the latest ITE Law provides a broader legal basis and adapts to technological developments, there are still several problems in its implementation, such as the inability of law enforcement officials in the field of digital forensics, overlapping regulations, and the lack of digital literacy of the community. Therefore, institutional strengthening, improving the technical capabilities of law enforcement officials, and updating legal policies are needed to respond to the development of cybercrime in the computer and internet era.